The Impact of Informal Institutions on Ensuring the Resilience of the National Economy - Alina BOIKO; Diana SHKUROPADSKA (Communications of International Proceedings, 2021)
Just in the last decades, the world has experienced a string of extreme shocks and natural disasters, including a global financial and economic crisis, a volcanic eruption in Iceland, a disastrous tsunami in Japan, political upheavals in North Africa and the Middle East, and COVID-19 pandemic. The speed and frequency of various shocks in the global economy have raised questions about building and ensuring the resilience of national economies. The resilience of the economic system is a necessary modern condition for economic growth and society’s development in today’s tightly connected global economy. The article identifies and analyzes informal institutions for ensuring the resilience of the national economy. Indicators for evaluating such informal institutions as the institute of trust in government, the institute of corruption perceptions, and the institute of economic culture have been identified. Generalization of the theoretical bases of resilience theory of the national economy in the face of external shocks, identification causes of low level of the Ukrainian economic resilience on the basis of institutional economics allowed the authors to formulate the system of interaction of formal and informal institutions of ensuring the resilience of the national economy.
Keywords: Economic Resilience; Trust; Corruption; Education; Financial Literacy